Analisis Usaha Event Organizer MICE (Meeting, Incentive, Conference, Exhibition) Melalui Kanvas Model Bisnisdan Peta Empati: Studi Kasus Event Organizer di Yogyakarta dan Surakarta. - Nadzir, Muhammad Miftahun (Universitas Muhammadiyah Yogyakarta, 2016)
In 2013, the Ministry of Tourism and Creative Economy stated Yogyakarta and Surakarta as a destination city of MICE in Indonesia. Data from Tourism Department of DIY 2011 shows, the implementation of MICE event recorded 4,509 times / year. In Surakarta, according to GTZ (2009), during the period between 2007-2009 MICE events that has been held as many as 12,981 activities. From these data shows that there is a potential opportunity to enter in this MICE industry. By using the business model canvas and empathy map, this event organizer's business analysis is expected to provide a comprehensive overview so that business actors in this field are able to fulfill the market demand and achieve sustainable competitive advantage.